Mitochondrial dysfunction and mitophagy in Parkinson's: from familial to sporadic disease. - Ryan, B; Hoek, S; Fon, E; Wade-Martins, R (Elsevier, 2015)
Parkinson's disease (PD) is a progressive neurodegenerative disorder characterised by the preferential loss of dopaminergic neurons in the substantia nigra. Mitochondrial dysfunction is increasingly appreciated as a key determinant of dopaminergic neuronal susceptibility in PD and is a feature of both familial and sporadic disease, as well as in toxin-induced Parkinsonism. Recently, the mechanisms by which PD-associated mitochondrial proteins phosphatase and tensin homolog deleted on chromosome 10 (PTEN)-induced putative kinase 1 (PINK1) and parkin function and induce neurodegeneration have been identified. In addition, increasing evidence implicates other PD-associated proteins such as α-synuclein (α-syn) and leucine-rich repeat kinase 2 (LRRK2) in mitochondrial dysfunction in genetic cases of PD with the potential for a large functional overlap with sporadic disease. This review highlights how recent advances in understanding familial PD-associated proteins have identified novel mechanisms and therapeutic strategies for addressing mitochondrial dysfunction in PD.